2023
DOI: 10.1021/acs.bioconjchem.3c00167
|View full text |Cite
|
Sign up to set email alerts
|

Break to Build: Isothermal Assembly of Nucleic Acid Nanoparticles (NANPs) via Enzymatic Degradation

Abstract: The intrinsic properties of RNA and DNA biopolymers emphasized by engineered nucleic acid nanoparticles (NANPs) offer accelerated development of next-generation therapies. The rational design of NANPs facilitates programmable architectures intended for regulated molecular and cellular interactions. The conventional bottom-up assembly of NANPs relies on the thermal annealing of individual strands. Here, we introduce a concept of nuclease-driven production of NANPs where selective digestion of functionally inert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In our study, we conduct a series of experiments to assess whether DNA triangles with various ssT regions would elicit an immune response or prove to be toxic to human cells. We utilize three different reporter cell lines (HEK-Blue hTLR7, HEK-Blue hTLR9, and HEK-Lucia RIG-I) engineered to turn up the activation of specific pathways related to the detection of exogenous nucleic acids. While TLR9 is a well-known key receptor for the recognition of DNA, TLR7 primarily recognizes ssRNAs. However, it has been reported that TLR7 also has the ability to respond to deoxyguanosine, independent of RNA. , Furthermore, recent studies have indicated the possible recognition of DNA nanoparticles by TLR7 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we conduct a series of experiments to assess whether DNA triangles with various ssT regions would elicit an immune response or prove to be toxic to human cells. We utilize three different reporter cell lines (HEK-Blue hTLR7, HEK-Blue hTLR9, and HEK-Lucia RIG-I) engineered to turn up the activation of specific pathways related to the detection of exogenous nucleic acids. While TLR9 is a well-known key receptor for the recognition of DNA, TLR7 primarily recognizes ssRNAs. However, it has been reported that TLR7 also has the ability to respond to deoxyguanosine, independent of RNA. , Furthermore, recent studies have indicated the possible recognition of DNA nanoparticles by TLR7 .…”
Section: Resultsmentioning
confidence: 99%
“…There have been several profound studies on bioproduction of ssDNA oligonucleotides. 119 Combining isothermal assembly assisted by enzymes 120 and kinetics control, it may be feasible to harvest designed DNA nanomachines with microbial production in a prescribed manner. With the fast developed computer-aided sequence design with cross-linked reactions and a sufficient supply of DNA materials, we believe DNA-enabled synthetic nanomachines with spatial and temporal controls can accomplish specified assignments in real-life biomedical and clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…For gene-editing applications where cleavage precision is paramount, higher fidelity is first required before the photoresponsive I-TevI nuclease can be fully exploited. The modular I-TevI nuclease is however well suited for in vitro purposes and may have applications for controlling the top-down synthesis of DNA nanostructures for 2D and 3D DNA architectures and microarrays and the release of molecular payloads from DNA-based precursors. , As these applications typically do not require high fidelity, the light-responsive I-TevI nuclease developed here could be applied without further engineering for optical control. In summary, we have demonstrated that monomeric homing endonucleases can be reengineered for optical control with programmable specificity by fusion of independent functional domains to LOV domain photoreceptors with notable dynamic range for a first-generation platform.…”
Section: Discussionmentioning
confidence: 99%